Beta cell function and insulin sensitivity in obese youth with maturity onset diabetes of youth mutations vs type 2 diabetes in TODAY: Longitudinal observations and glycemic failure - Arslanian, Silva (Pediatr Diabetes, 2020)
OBJECTIVE: In treatment options for type 2 diabetes in adolescents and youth (TODAY), 4.5% of obese youth clinically diagnosed with type 2 diabetes (T2D) had genetic variants consistent with maturity onset diabetes of youth (MODY) diagnosis. The course of IS and β-cell function in obese youth with MODY remains unknown. In this secondary analysis, we examined IS and β-cell function in MODY vs. non-MODY obese youth at randomization and over time. METHODS: Genetic data in TODAY included 426 non-MODY (T2D) and 22 MODY youth (7 glucokinase MODY mutation positive [GCK-MODY], 12 hepatocyte nuclear factor MODY mutation positive [HNF-MODY], 2 Insulin gene mutation [insulin (INS)-MODY], and 1 Kruppel-like factor 11 [KLF11-MODY]). Oral glucose tolerance test (OGTT)-derived IS, C-peptide index, and β-cell function relative to IS oral disposition index (oDI) was measured at randomization, and over 24 months in addition to total and high-molecular-weight adiponectin (HMWA). RESULTS: At randomization, IS, total adiponectin, and HMWA were significantly higher in the two MODY groups than in non-MODY. β-cell function measured by C-peptide oDI was 3-fold higher in GCK-MODY than in HNF-MODY and 1.5-fold higher than non-MODY (P for both <.05) Glycemic failure rate was 75.0% in HNF-MODY, 46.9% in non-MODY, and zero in GCK-MODY youth. While the changes in IS and oDI were not different among the three groups in the first 6 months, IS improved from 6 to 24 months in HNF-MODY vs GCK-MODY youth. CONCLUSIONS: In TODAY, β-cell function at randomization was worse in obese HNF-MODY youth compared with GCK-MODY youth, while insulin sensitivity was worse in non-MODY compared with the other two MODY groups. Over time, IS showed the greatest improvement in HNF-MODY youth. This raises the possibility that TODAY therapeutic modalities of insulin sensitization in these obese HNF-MODY youth may have played a beneficial role.